Effects of napping on cognitive function modulation in elderly adults with a morning chronotype: A nationwide survey. (9th July 2018) - Fang, Su‐Chen; Huang, Chun‐Jen; Wu, Yu‐Lin; Wu, Pei‐Yu; Tsai, Pei‐Shan
Abstract: Circadian rhythms and napping habits have been associated with cognitive function; however, little is known about the interaction effects on cognitive function. The present study examined the moderating effects of napping habits on the relationship between chronotypes and cognitive function decline in elderly adults. This cross‐sectional study analysed data from the 2009 Taiwan National Health Interview Survey. A total of 1, 724 elderly adults (aged ≥65 years) were included. Cognitive function was determined by the Mini‐Mental State Examination. Participants' chronotypes were assessed using the midpoint of sleep. Napping habits were assessed by self‐report questions. Demographic data, health‐related factors and sleep characteristics of the participants were also assessed as potential confounding factors. A hierarchical regression will be used to test the moderating role of napping habits in the relationship between chronotype and cognitive function level after adjustment for potential confounders. A significant interaction effect between chronotype and napping habits was observed with the MMSE score ( b  = −0.29, SE  = 0.14, p =  0.03). Morning‐type elderly patients with nap durations >60 min exhibited significantly higher MMSE scores than non‐nappers ( F =  7.48; p =  0.00). This nationwide survey confirms that in morning‐type elderly adults, nap durations >60 min are associated with less cognitive decline; however, napping habits are not associated with cognitive function level in evening‐type and intermediate‐type elderly adults.